Development of a plasma activated multifunctional polyester fabric using zinc oxide nanoparticles and citronella oil microcapsules - Mehravani, Behnaz (2022)
Apresentação efetuada na 21th World Textile Conference - AUTEX 2022, em Lodz, Poland, 2022